Single-phase niobate, active electrode material and preparation method and application of active electrode material

By developing a single-phase niobate anode material with a large titanium and a small niobium, and using the liquid phase method to prepare and optimize its crystal structure, the safety hazards and insufficient performance problems of existing lithium-ion battery anode materials during high-ratio charging and discharging are solved, and high-performance and low-cost battery materials are achieved.

CN119569117AActive Publication Date: 2025-03-07HUNAN NAIMING NEW MATERIALS TECHNOLOGY CO LTD

Patent Information

Application Number
CN202411745960.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-29
Publication Date
2025-03-07
Estimated Expiration
2044-11-29

AI Technical Summary

Technical Problem

The existing lithium-ion battery anode materials have safety hazards and insufficient performance when charging and discharging at high rates, especially the low safety and low rate performance of graphite materials, and the high niobium content of existing niobate hinders its industrialization process.

Method used

A single-phase niobate with more titanium and less niobium was developed, prepared by liquid phase method, with a niobium content significantly lower than that of traditional TiNb2O7, and introduced cationic gaps and oxygen ion vacancies into the crystal structure, which were in the thermodynamic metastable state, thereby improving its electrochemical performance.

Benefits of technology

It realizes high safety, reversible specific capacity, rate performance, cycle performance and temperature adaptability of lithium-ion battery negative electrode materials, while reducing production costs and being suitable for industrial applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119569117A_ABST
    Figure CN119569117A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of inorganic non-metallic materials, electrochemistry, material chemistry and chemical power supply products, and particularly relates to a single-phase niobate and an active electrode material of a lithium ion battery as well as a preparation method and application of the single-phase niobate and the active electrode material. The single-phase niobate provided by the invention has a chemical formula of TixNbyOz (0.15 < = x / z < = 0.25 and 0.20 < = y / z < = 0.28) and has the characteristics of more titanium and less niobium. The single-phase niobate provided by the invention is prepared by adopting a liquid phase method based on a precursor solution, can be properly post-processed, has high safety performance, specific capacity, first-week coulombic efficiency, rate capability, cycle performance and temperature adaptability when being used for a negative electrode of a lithium ion battery, and is relatively low in cost. The preparation method of the active electrode material provided by the invention is simple, and the active electrode material has a wide application prospect in the field of ultra-fast charging and high-power lithium ion batteries. More choices are provided for the active negative electrode material of the lithium ion battery, and rapid development of the high-performance lithium ion battery can be greatly promoted.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of inorganic non-metallic materials, electrochemistry, material chemistry and chemical power supply products, and more specifically, relates to a single-phase niobate of a lithium-ion battery, an active electrode material and a preparation method and application thereof. Background Art

[0002] Lithium-ion batteries have been widely and rapidly used in various fields of human life, from consumer electronics to electric vehicles and large-scale energy storage, due to their advantages such as high energy output, high conversion efficiency, long service life and low self-discharge. It is expected that the global market for lithium-ion batteries will grow at an annual rate of 20% to 30% by 2030. In this context, people have put forward higher requirements for lithium-ion batteries, such as safety, stability, high energy, weather resistance and ultra-fast charging capabilities, in order to meet the urgent needs of emerging application fields such as hybrid electric vehicles, start-stop power supplies, high-end electric motorcycles, electric engineering vehicles, electric buses, electric logistics vehicles, baseband processing power supplies (BBU), warehouse robot power tools, drones, electric ships, military, and frequency and peak-valley regulation in grid-connected energy storage systems.

[0003] Lithium-ion batteries are mainly composed of four parts: positive electrode, negative electrode, diaphragm and electrolyte. The charging and discharging principle is essentially Li + Through the transport of electrolyte solution, reversible extraction and embedding are carried out in the negative and positive electrode materials, accompanied by the mutual conversion between chemical energy and electrical energy. Take the lithium-ion battery composed of LiCoO2 as the positive electrode and graphite as the negative electrode as an example. During the charging process, Li + From the positive electrode material, releasing an electron, Co 3+ Oxidized to Co 4+ , Li + The electrolyte is transported through the diaphragm and embedded into the graphite negative electrode. At the same time, the graphite obtains an electron to maintain charge balance. During the discharge process, Li + It is released from the graphite of the negative electrode material and embedded in the positive electrode material. 4+ Reduction to Co 3+ The battery charging rate is usually expressed as a "rate". 1C charging refers to the charging current that fully charges the battery in 1 hour, and 10C charging refers to the charging current that fully charges the battery in 1 / 5 hour (12 minutes).

[0004] As one of the core components of lithium-ion batteries, the negative electrode materials that have been commercialized mainly include carbon (including silicon carbon) and lithium titanate (Li4Ti5O 12 Carbon materials (represented by graphite) have a high reversible specific capacity (about 300–360 mAh g – 1), low cost and long cycle life, it is widely used in small electronic devices. However, graphite has safety issues that cannot be ignored. The working potential of graphite is very low (<0.2V vs.Li / Li + ), a large overpotential will be generated when charging and discharging at a larger rate (≥5C), which will easily produce lithium dendrites. The formation of lithium dendrites greatly increases the probability of battery short circuit, which brings serious safety hazards. In addition, the lithium ion diffusion rate of graphite is not high, resulting in poor rate performance. These problems seriously limit its application in high-performance lithium-ion batteries. Adding silicon or silicon compounds to carbon materials to form silicon-carbon negative electrode materials increases the specific capacity of the negative electrode materials, but fails to solve the above problems of carbon materials. Li4Ti5O 12 Has a very safe and stable working platform (1.5–1.6V vs.Li / Li + ) and excellent cycle performance. After modification (usually nano- and carbon-coated) Li4Ti5O 12 It can achieve fast charge and discharge. However, Li4Ti5O 12 Small reversible specific capacity (only 160–170 mAh g – 1 ) and low tap density make it difficult to use in high energy density lithium-ion batteries. Therefore, it is very important and urgent to develop lithium-ion battery negative electrode materials with high safety, reversible specific capacity, rate performance (≥5C), cycle performance and temperature adaptability.

[0005] Niobates (or niobium-based mixed oxides) were first identified as potential anode materials in academic literature in 1983, but attracted limited interest at the time due to the lack of commercial cathode materials that matched their rate performance. It was not until 2011 that interest in niobate anode materials was revived, with the use of titanium niobate TiNb2O7 as anode material and commercial LiNi 0.5 Mn 1.5 O4 was used as the positive electrode material in the battery experiment, which showed that the battery has significant advantages in fast charging capability, cycle life and volume energy density. Since then, a variety of new niobate negative electrode materials have been developed, including Ti2Nb 10 O 29 、TiNb 24 O 62 and other non-titanium niobate niobates. These niobates can achieve high safety, reversible specific capacity, rate performance (≥5C), cycle performance and temperature adaptability either intrinsically or after modification (such as carbon coating).

[0006] However, among the existing niobates, TiNb2O7 contains a relatively low amount of niobium (76.8wt%, calculated as Nb2O5, the same below), while other niobates generally contain >89% niobium, such as Ti2Nb 10 O 29 The niobium content is 89.3wt%, TiNb 24 O 62 The niobium content of TiNb2O7 is 97.6wt%. The relatively low niobium content and cheap titanium raw materials make the cost of TiNb2O7 significantly lower than other niobates, so TiNb2O7 has received widespread attention and a lot of basic and applied research. However, the niobium content of TiNb2O7 is still relatively high, which obviously hinders the industrialization process of niobates. Therefore, the development of niobates with lower niobium content than TiNb2O7 is the key and urgent requirement for the industrialization of niobates. Summary of the invention

[0007] In view of the problem that the comprehensive performance of existing commercial negative electrode materials for lithium-ion batteries is poor, the purpose of the present invention is to provide a lithium-ion battery active electrode material with excellent comprehensive performance - high-titanium-low-niobium niobate, which has high safety performance, specific capacity, first-cycle coulombic efficiency, rate performance, cycle performance and temperature adaptability, and has low cost.

[0008] The present invention also provides a method for preparing the single-phase niobate. The present invention also provides an active electrode material containing the single-phase niobate.

[0009] Another object of the present invention is to provide applications of the above-mentioned single-phase niobate or active electrode material.

[0010] The technical solution adopted by the present invention to achieve the above-mentioned purpose is:

[0011] In a first aspect, the present invention provides a general formula Ti x Nb y O z A single-phase niobate wherein 0.15≤x / z≤0.25 and 0.20≤y / z≤0.28; preferably, 0.171≤x / z≤0.215 and 0.228≤y / z≤0.263. The exact values ​​of x, y and z within the defined ranges can be selected to provide a charge-balanced crystal structure. Typical compositions are Ti 1.5 Nb 1.6 O7、Ti 1.4 Nb 1.68 O7、Ti 1.3 Nb 1.76 O7 and Ti 1.2 Nb 1.84 O7.

[0012] Compared with the traditional TiNb2O7, the Tix NbyOz has the characteristics of "more titanium and less niobium", and is a single-phase material rather than a multi-phase material. Based on the considerations of defect chemical charge balance, particle number balance and position balance, the crystal structure of the TixNbyOz of the present invention retains the TiNb2O7 crystal structure (the crystal structure unit is a 3×3 octahedron connected in order by common edges and common points) while containing cation gaps (at least one of Ti ion gaps and Nb ion gaps) and oxygen ion vacancies, and is in a thermodynamic metastable state. Since the niobium content of the TixNbyOz of the present invention is significantly lower (for example, the niobium content of Ti1.5Nb1.6O7 is only 63.9wt%, which is 16.8% lower than that of TiNb2O7), this significantly reduces the cost of niobates, which is very beneficial to the industrialization of niobates.

[0013] The reversible specific capacity of the poly-titanium-poor-niobium niobate active electrode material of the present invention can be 270-300 mAh / g, or even greater. Here, the specific capacity is defined as the specific capacity tested in the second cycle of a half-cell constant current cycle experiment with a voltage window of 0.8-3.0 V vs. Li / Li+ at a rate of 0.1C. Active materials with large specific capacity have the advantage of improving the performance of electrochemical devices. Providing an active electrode material with a large specific capacity can improve the energy density and power density of an electrochemical device containing the active electrode material.

[0014] The poly-titanium-poor-niobium niobate active electrode material of the present invention may have an appropriate voltage distribution measured at a voltage window of 0.8-3.0V vs. Li / Li+ at a rate of 0.1C in the second cycle of a half-cell constant current cycle test, and an average working potential of 1.4-1.7 vs. Li / Li+. When the lithium insertion voltage is between 2.0V and 0.8V, the specific capacity of the material is greater than 240mAh g-1, and when the lithium removal voltage is between 0.8V and 2.0V, the specific capacity of the material is greater than 240mAh g-1. Providing an active electrode material with a higher working voltage can improve the safety performance of an electrochemical device containing the active electrode material.

[0015] The poly-titanium-poor-niobium niobate active electrode material of the present invention can have a first-cycle coulombic efficiency of 85-98%, usually 90-95%. Here, the first-cycle coulombic efficiency is obtained by testing the voltage window of 0.8-3.0V vs. Li / Li+ at a rate of 0.1C in the first cycle of a half-cell constant current cycle test. The present invention provides an active electrode material with a higher first-cycle coulombic efficiency, which can improve the energy density and power density of an electrochemical device containing the active electrode material.

[0016] The poly-titanium-poor-niobium niobate active electrode material of the present invention can have a capacity retention rate greater than 80%, usually above 85%. Here, the capacity retention rate is obtained by testing the voltage window of 0.8-3.0V vs. Li / Li+ at a charge and discharge rate of 5C (the charge rate and the discharge rate are equal) in 500 cycles of a half-cell constant current cycle test. Providing an active electrode material with a higher capacity retention rate can improve the cycle performance of an electrochemical device containing the active electrode material.

[0017] The poly-titanium-poly-niobium niobate active electrode material of the present invention can have a Li+ diffusion rate greater than 10-12 cm2 s-1. The present invention provides an active electrode material with a high Li+ diffusion rate to improve the rate (fast charge) performance of an electrochemical device containing the active electrode material.

[0018] The poly-titanium-poor-niobium niobate active electrode material of the present invention can have an electrode density of 2.5 g cm-3 or even higher after rolling. The material achieves an electrode density of up to 3.0 g cm-3 or even higher after rolling. Providing a material with a higher electrode density can improve the energy density of an electrochemical device containing the active electrode material. Specifically, when the electrode density is high, a high volume capacity can be achieved, which is based on volume capacity = mass capacity × electrode density × active material ratio.

[0019] The poly-titanium-poly-niobium niobate active electrode material of the present invention may further contain Li. In other words, the active electrode material may be a lithiated active electrode material. The active electrode material may be represented by the general formula LiλTixNbyOz, where x, y and z satisfy the above ranges, wherein λ is selected to provide charge balance.

[0020] The active electrode material may include a large number of primary particles (sometimes called crystallites). The average particle size of the primary particles may be from 10 nm to 10 μm, preferably from 100 nm to 5 μm, although the most ideal particle size of the primary particles depends on their use. For example, when the active electrode material is intended for use in high-power batteries, smaller primary particles (e.g., less than 100 nm) may be advantageous. If the active electrode material is used to develop high-energy batteries, larger particle sizes (e.g., 1–5 μm) may be advantageous. These primary particles may be partially or completely aggregated into secondary particles. Secondary particles are generally porous. In some cases, these primary particles are substantially non-agglomerated. When some or all of the primary particles are aggregated into secondary particles, the average size of the secondary particles is 0.5–30 μm, preferably 2–20 μm, although the most ideal particle size of the secondary particles depends on their use. For example, in cases where the active electrode material is used in high-power batteries, smaller secondary particles (1.5–5 μm, or even smaller than 1.5 μm) may be advantageous. Where the active electrode material is intended for use in the development of high energy batteries, larger secondary particles (8-20 μm, or even larger) may be advantageous. The particle size of the primary and secondary particles may be measured using any known conventional technique (e.g., electron microscopy imaging and laser particle size analysis).

[0021] The active electrode material may form a carbon coating on the surface of the primary particles and the secondary particles. For the secondary particles, the carbon may be coated into the voids of the secondary particles. The carbon coating may include graphitic carbon. The carbon coating may be performed by chemical vapor deposition, organic pyrolysis, ball milling and mixing. The content of the coated carbon may be less than 5 wt %, preferably less than 2 wt %, and more preferably less than 1 wt % based on the total weight of the active electrode material.

[0022] In a second aspect, the present invention provides an electrochemical device comprising a negative electrode, a positive electrode, and an electrolyte and a separator disposed between the negative electrode and the positive electrode, wherein the negative electrode comprises an active electrode material developed according to the first aspect of the present invention. The electrolyte may be a liquid electrolyte. An alternative or additional electrolyte may be a solid electrolyte. The separator may be a polymer separator or a ceramic separator. Conductive agents and adhesives may be further added to the negative electrode. For example, the negative electrode is composed of 80wt% active material, 10wt% conductive agent, and 10wt% binder. Alternatively, the negative electrode is composed of 92wt% active material, 4wt% conductive agent, and 4wt% binder. The amount of active electrode material in the negative electrode may be between 70wt% and 99wt%, preferably between 80wt% and 98wt%, and more preferably between 90wt% and 96wt%.

[0023] In the third aspect, the present invention provides an active electrode material according to the first aspect of the present invention applied to a negative electrode as a negative electrode active material or as a component of a negative electrode active material, and combined with a positive electrode, an electrolyte and a separator for use in charging and discharging a lithium ion battery.

[0024] In a fourth aspect, the present invention provides a method for processing an active electrode material as an active negative electrode material or a component of a negative electrode active material for use in a lithium ion battery according to the first aspect of the present invention, wherein the method comprises diffusing lithium ions into the negative electrode active material.

[0025] In a fifth aspect, the present invention provides a liquid phase method for preparing a single-phase niobate of the general formula TixNbyOz according to the first aspect of the present invention, the method comprising the following steps:

[0026] 1. Dissolve the titanium source and niobium source raw materials in any one of water, alcohol and alcohol-water solvent to form a solution;

[0027] 2. The solution is treated by any one of spray drying, solvothermal method, sol-gel method, direct evaporation method and coprecipitation method to obtain a precursor powder.

[0028] 3. Sintering the precursor powder at a temperature in the range of 700-1200°C to form an active electrode material.

[0029] Here, the titanium source and niobium source raw materials are titanium compounds and niobium compounds that are soluble in water or alcohol. For the titanium source raw material, water-soluble titanyl sulfate, titanium chloride, and ethanol-soluble tetraisopropyl titanate and tetrabutyl titanate can be selected. For the niobium source raw material, water-soluble niobium oxalate (including hydrated niobium oxalate), ammonium niobium oxalate (including hydrated ammonium niobium oxalate), and ethanol-soluble niobium chloride and ethanol niobium can be selected. The titanium source and niobium source raw materials are dissolved in any one of water, alcohol and alcohol-water solvents to form a solution to achieve complete mixing of titanium ions and niobium ions at the atomic / molecular level, which is crucial for the preparation of poly-titanium-less-niobium niobate (metastable, containing at least one defect of cation interstitial and oxygen ion vacancies). In contrast, the traditional solid-phase sintering method of preparing TiNb2O7 by ball-milling and mixing titanium dioxide (TiO2) and niobium pentoxide (Nb2O5) and then sintering cannot prepare poly-titanium-less-niobium niobate, because the niobate obtained by this traditional solid-phase sintering method is in a thermodynamically stable state.

[0030] When the present invention adopts a liquid phase method to prepare single-phase niobate, the alcohol used includes but is not limited to ethanol, and may also be other alcohols, such as isopropanol, butanol, and ethylene glycol.

[0031] The step of sintering the precursor powder can be maintained for 0.5 hours to 24 hours, more preferably 2 hours to 10 hours. For example, the sintering step can last for 2 hours to 10 hours or even longer. The sintering step can be performed for 24 hours to 10 hours, or even shorter.

[0032] In some methods, it may be beneficial to perform a sintering process. For example, the precursor powder may be heated at a first heating temperature for a certain time, and then heated at a second heating temperature for a certain time. Generally, the second heating temperature is higher than the first heating temperature. Performing such a two-step sintering can help the solid phase reaction form the desired crystal structure.

[0033] The step of sintering the precursor powder can be carried out in a gaseous atmosphere. The gaseous atmosphere can be an inert atmosphere, a reducing atmosphere, or an oxidizing atmosphere. In the case where it is desired to produce an oxygen-deficient material, it is preferred to sinter the precursor material in an inert or reducing atmosphere. Suitable gas environments include: air, O2, N2, Ar, He, CO2, CO, H2, and mixtures thereof.

[0034] The method may require one or more steps of post-treatment of the formed poly-titanium-less-niobium niobate. In some cases, the method may include a post-treatment step of heat-treating the poly-titanium-less-niobium niobate, sometimes referred to as "annealing". The post-treatment heat treatment step may be performed in an atmosphere different from that of the sintered precursor powder. The post-treatment heat treatment step may be performed in an inert or reducing gas atmosphere. Such a post-treatment heat treatment step may be performed at a temperature above 500°C, such as 700°C. The post-treatment heat treatment step may be beneficial for forming more defects in the active electrode material. In some cases, the method may include mixing the poly-titanium-less-niobium niobate with a carbon source to form a carbon coating on the poly-titanium-less-niobium niobate. The mixture of the poly-titanium-less-niobium niobate and the carbon source may be heated to form a carbon coating on the poly-titanium-less-niobium niobate. Suitable carbon sources include, but are not limited to, carbohydrate materials (e.g., sugars, polymers), conductive carbon (e.g., carbon black), and aromatic carbon materials (e.g., asphalt carbon). The poly-titanium-less-niobium niobate may also be carbon coated by chemical vapor deposition or organic pyrolysis. A preferred method of carbon coating is to grind the active electrode material with a carbon source, and then heat the active electrode material and the carbon source in a furnace under an inert or reducing atmosphere, so that the carbon source is pyrolyzed into carbon and then coated on the surface of the polytitanium-less niobium niobate particles. Another preferred method of forming a carbon coating includes mixing the polytitanium-less niobium niobate with a carbon source, dispersing the polytitanium-less niobium niobate and the carbon source in an aqueous slurry, and then spray drying. The polytitanium-less niobium niobate and the carbon source are then heated in a furnace under an inert or reducing atmosphere, so that the carbon source is pyrolyzed into carbon and then coated on the surface of the polytitanium-less niobium niobate particles. If the carbon source is conductive carbon, there is no need to pyrolyze the material after spray drying. In some cases, the method may include a step of grinding the polytitanium-less niobium niobate to change the particle size of the polytitanium-less niobium niobate. For example, the polytitanium-less niobium niobate can be processed by one or more processes, including air flow milling, screening, or ball milling. This can provide a more suitable particle size for the desired application of the polytitanium-less niobium niobate. In addition, conventional modification methods (doping, compounding and nano-crystallization, etc.) can also be used to modify the poly-titanium-poly-niobium niobate. For example, for doping modification, it is only necessary to add a small amount of water- or alcohol-soluble compounds containing doping elements during the material preparation process.

[0035] The present invention includes any combination of the above-mentioned aspects and preferred features, unless such a combination is explicitly not permitted.

[0036] The beneficial effects of the present invention are:

[0037] (1) The high-titanium-low-niobium niobate active electrode material provided by the present invention is applied to the negative electrode of a lithium-ion battery, which not only has a series of advantages such as high specific capacity, safety performance, first-cycle coulombic efficiency, rate performance and cycle performance, but also has low cost and is suitable for industrial production.

[0038] (2) The preparation method of the high-titanium-low-niobium niobate provided by the present invention is simple, and the battery assembled with other battery components is suitable for safe, stable, high-energy, weather-resistant, and ultra-fast charging applications, including hybrid electric vehicles, start-stop power supplies, high-end electric motorcycles, electric engineering vehicles, electric buses, electric logistics vehicles, baseband processing power supplies (BBU), warehouse robot power tools, drones, electric ships, military, and frequency and peak-valley regulation in grid-connected energy storage systems, etc., and has a very broad application prospect. The present invention provides more choices for active negative electrode materials of lithium-ion batteries, which can greatly promote the rapid development of high-performance lithium-ion batteries. BRIEF DESCRIPTION OF THE DRAWINGS

[0039] Figure 1 The X-ray diffraction (XRD) pattern of the Ti1.5Nb1.6O7 porous microspheres obtained in Example 1;

[0040] Figure 2 This is a scanning electron microscope (SEM) photograph of the Ti1.5Nb1.6O7 porous microspheres obtained in Example 1;

[0041] Figure 3 The charge and discharge curves of the Ti1.5Nb1.6O7 / Li half-cell obtained in Example 1 at different rates;

[0042] Figure 4 This is a cycle performance diagram of the Ti1.5Nb1.6O7 / Li half-cell obtained in Example 1 at a 5C rate;

[0043] Figure 5 X-ray diffraction (XRD) pattern of Ti1.4Nb1.68O7 porous microspheres obtained in Example 2;

[0044] Figure 6 This is a scanning electron microscope (SEM) photograph of the Ti1.4Nb1.68O7 porous microspheres obtained in Example 2;

[0045] Figure 7 The charge and discharge curves of the Ti1.4Nb1.68O7 / Li half-cell obtained in Example 2 at different rates;

[0046] Figure 8 This is a cycle performance diagram of the Ti1.4Nb1.68O7 / Li half-cell obtained in Example 2 at a 5C rate;

[0047] Fig. 9 This is the X-ray diffraction (XRD) pattern of the Ti1.6Nb1.52O7 particles obtained in Example 3;

[0048] Fig.10 This is a scanning electron microscope (SEM) photograph of the Ti1.6Nb1.52O7 particles obtained in Example 3;

[0049] Fig.11 The charge and discharge curves of the Ti1.6Nb1.52O7 / Li half-cell obtained in Example 3 at different rates;

[0050] Fig.12 This is a cycle performance diagram of the Ti1.6Nb1.52O7 / Li half-cell obtained in Example 3 at a 5C rate;

[0051] Fig.13 This is the X-ray diffraction (XRD) pattern of the Ti1.3Nb1.76O7 particles obtained in Example 4;

[0052] Fig.14 This is a scanning electron microscope (SEM) photograph of the Ti1.3Nb1.76O7 particles obtained in Example 4;

[0053] Fig.15 The charge and discharge curves of the Ti1.3Nb1.76O7 / Li half-cell obtained in Example 4 at different rates;

[0054] Fig.16 This is a cycle performance diagram of the Ti1.3Nb1.76O7 / Li half-cell obtained in Example 4 at a 5C rate;

[0055] Fig.17 This is the X-ray diffraction (XRD) pattern of the Ti1.2Nb1.84O7 porous microspheres obtained in Example 5;

[0056] Fig.18 This is a scanning electron microscope (SEM) photograph of the Ti1.2Nb1.84O7 porous microspheres obtained in Example 5;

[0057] Fig.19 The charge and discharge curves of the Ti1.2Nb1.84O7 / Li half-cell obtained in Example 5 at different rates;

[0058] Fig. 20 This is a cycling performance diagram of the Ti1.2Nb1.84O7 / Li half-cell obtained in Example 5 at a 5C rate;

[0059] Fig.21 is the X-ray diffraction (XRD) pattern of the TiNb2O7 micron particles obtained in Comparative Example 1;

[0060] Fig. 22 This is a scanning electron microscope (SEM) photograph of the TiNb2O7 micron particles obtained in Comparative Example 1;

[0061] Fig.23 The charge and discharge curves of the TiNb2O7 / Li half-cell obtained in Comparative Example 1 at different rates;

[0062] Fig.24 This is the cycle performance diagram of the TiNb2O7 / Li half-cell obtained in Comparative Example 1 at a rate of 5C;

[0063] Fig.25 X-ray diffraction (XRD) pattern of TiNb2O7 porous microspheres obtained in Comparative Example 2;

[0064] Fig.26 This is a scanning electron microscope (SEM) photograph of the TiNb2O7 porous microspheres obtained in Comparative Example 2;

[0065] Fig. 27 The charge and discharge curves of the TiNb2O7 / Li half-cell obtained in Comparative Example 2 at different rates;

[0066] Fig.28 This is a transmission electron microscope (TEM) photograph of the carbon-coated Ti1.5Nb1.6O7 (C-Ti1.5Nb1.6O7) porous microspheres obtained in Example 25;

[0067] Fig.29 The charge and discharge curves of the C-Ti1.5Nb1.6O7 / Li half-cell obtained in Example 25 at different rates;

[0068] Fig.30 This is a cycling performance diagram of the C-Ti1.5Nb1.6O7 / Li half-cell obtained in Example 25 at a 5C rate;

[0069] Fig.31 The charge and discharge curves of the LiNi0.5Mn1.5O4 / Ti1.5Nb1.6O7 full battery obtained in Example 26 at different rates;

[0070] Fig.32 This is the cycling performance diagram of the LiNi0.5Mn1.5O4 / Ti1.5Nb1.6O7 full battery obtained in Example 26 at 7C rate. DETAILED DESCRIPTION

[0071] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention.

[0072] Example 1: Preparation of high-titanium and low-niobium niobate by spray drying

[0073] 0.03 mol of titanyl sulfate and 0.032 mol of niobium oxalate (hydrated) were dissolved in 300 mL of deionized water and stirred to form a uniform aqueous solution.1.5 Nb 1.6 The inlet temperature of the spray dryer was set at 180°C, the outlet temperature was set at 84°C, the flow rate of the peristaltic pump was set at 20 rpm, and the above aqueous solution was spray dried to obtain Ti 1.5 Nb 1.6 O7 precursor powder. The obtained precursor powder is placed in a muffle furnace and sintered at 1050℃ for 4 hours to obtain Ti 1.5 Nb 1.6 O7 porous microspheres were sieved using a 300 mesh sieve.

[0074] Half-cell preparation and testing: 80 wt% of polytitanium-niobate, 10 wt% of binder (polyvinylidene fluoride) and 10 wt% of conductive carbon (acetylene black) were added to N-methylpyrrolidone and mixed to prepare a slurry. The slurry was coated on one side of a copper foil and dried. The fully dried electrode was rolled to obtain an active material loading of 4–5 mg cm – 2 The working electrode was then assembled into a CR2032 half-cell, in which the electrolyte was obtained by dissolving 1M lithium hexafluorophosphate in a mixed solvent of ethylene carbonate / diethylene carbonate / dimethyl carbonate (volume ratio of 1:1:1), the separator was made of glass fiber, and the counter electrode was a lithium sheet. The electrochemical test temperature was about 25°C. For each cycle of electrochemical testing, it was carried out in constant current mode with a voltage window of 0.8–3.0V vs.Li / Li+, the charge rate (charge current density) and the discharge rate (discharge current density) were equal, and 1C was set to 250mA g–1.

[0075] Figure 1 This is the X-ray diffraction (XRD) diagram of the Ti1.5Nb1.6O7 porous microspheres obtained in Example 1. Analysis shows that the Ti1.5Nb1.6O7 porous microspheres prepared by spray drying are a single-phase shear ReO3 type crystal structure, and have the same crystal structure unit as TiNb2O7 (3×3 octahedrons connected in order with common edges and common points). Figure 2 This is a scanning electron microscope (SEM) photograph of the Ti1.5Nb1.6O7 porous microspheres obtained in Example 1. It can be seen that the primary particle size of the Ti1.5Nb1.6O7 porous microspheres is between 0.1-0.4 μm, and the secondary particle size is between 0.5-2.5 μm. Figure 3 The charge and discharge curves of the Ti1.5Nb1.6O7 / Li half-cell at different rates obtained in Example 1. The reversible specific capacity of the Ti1.5Nb1.6O7 / Li half-cell with an active material loading of 5.01 mg cm-2 at 0.1C is 277 mAh g-1, the first cycle coulombic efficiency is 90.5%, and the reversible specific capacity at 5C is 147 mAh g-1. Figure 4 This is a cycling performance diagram of the Ti1.5Nb1.6O7 / Li half-cell obtained in Example 1 at a rate of 5C. The capacity retention rate of the Ti1.5Nb1.6O7 / Li half-cell with an active material loading of 5.01 mg cm-2 after 500 cycles at 5C is 83.1% (refer to the second cycle).

[0076] Example 2: Preparation of high-titanium and low-niobium niobate by solvent thermal method

[0077] 0.0035 mol of tetraisopropyl titanate and 0.0042 mol of niobium ethoxide were dissolved in 80 mL of ethanol and stirred to form a uniform ethanol solution. 1.4 Nb 1.68 O7 precursor powder. The above solution was transferred to a reactor with a volume of 100 mL, and the temperature was raised to 200°C (heating rate was 4°C / min) by external heating and maintained at 200°C for 24 hours. After the reaction was completed, the temperature was lowered to room temperature. The suspension in the reactor was separated by centrifugation to obtain solid powder and washed. The obtained precursor powder was placed in a muffle furnace and sintered at 800°C for 20 hours to obtain Ti 1.4 Nb 1.68 O7 porous microspheres. Use a 300 mesh sieve for sieving. The subsequent half-cell preparation and testing methods are the same as in Example 1.

[0078] Figure 5 The Ti obtained in Example 2 1.4 Nb 1.68 X-ray diffraction (XRD) pattern of O7 porous microspheres shows that Ti 1.4 Nb 1.68 The O7 porous microspheres are a single-phase shear ReO3 type crystal structure, and have the same crystal structural unit as TiNb2O7 (3×3 octahedrons connected in order with common edges and common points). Figure 6 The Ti obtained in Example 2 1.4 Nb 1.68 Scanning electron microscope (SEM) image of O7 porous microspheres shows that Ti 1.4 Nb 1.68 The primary particle size of O7 porous microspheres is between 0.05–0.2 μm, and the secondary particle size is between 0.5–3 μm. Figure 7 The Ti obtained in Example 2 1.4 Nb 1.68 Charge and discharge curves of O7 / Li half-cell at different rates. The active material loading is 4.96 mg cm – 2 Ti 1.4 Nb 1.68The reversible specific capacity of the O7 / Li half-cell at 0.1C is 282 mAh g – 1 The first cycle Coulombic efficiency is 94.0%, and the reversible specific capacity at 5C is 135 mAh g – 1 . Figure 8 The Ti obtained in Example 2 1.4 Nb 1.68 Cycling performance of O7 / Li half-cell at 5C rate. The active material loading is 4.96 mg cm – 2 Ti 1.4 Nb 1.68 The capacity retention rate of the O7 / Li half-cell after 500 cycles at 5C is 78.4% (refer to the second cycle).

[0079] Example 3: Preparation of high-titanium and low-niobium niobate by sol-gel method

[0080] 0.032 mol titanium chloride and 0.0304 mol niobium oxalate (hydrated) were dissolved in 500 mL ethanol-water (volume ratio 1:1) and stirred to form a uniform alcohol-water solution. 1.6 Nb 1.52 O7 precursor powder. Heat the above solution with a heater to allow hydrolysis to occur, obtain a gel-like solid, and continue to evaporate the solvent. The obtained solid is mixed with ethanol and ground in a planetary ball mill. The obtained slurry is filtered and washed with ethanol to obtain Ti 1.6 Nb 1.52 O7 precursor powder. The obtained precursor powder is placed in a muffle furnace and sintered at 950℃ for 12 hours to obtain Ti 1.6 Nb 1.52 O7 porous microspheres. Use a 300 mesh sieve for sieving. The subsequent half-cell preparation and testing methods are the same as in Example 1.

[0081] Fig. 9 The Ti obtained in Example 3 1.6 Nb 1.52 X-ray diffraction (XRD) pattern of O7 particles, analysis shows that Ti prepared by sol-gel method 1.6 Nb 1.52 The O7 particles are single-phase sheared ReO3 type crystal structures, and have the same crystal structural units as TiNb2O7 (3×3 octahedrons connected in order by common edges and common points). Fig.10 The Ti obtained in Example 3 1.6 Nb 1.52 Scanning electron microscope (SEM) photo of O7 particles shows that Ti 1.6 Nb 1.52The primary particle size of O7 particles is between 0.4–0.6 μm, and the secondary particle size is between 2–20 μm. Fig.11 The Ti obtained in Example 3 1.6 Nb 1.52 Charge and discharge curves of O7 / Li half-cell at different rates. The active material loading is 5.05 mg cm – 2 Ti 1.6 Nb 1.52 The reversible specific capacity of the O7 / Li half-cell at 0.1C is 283 mAh g – 1 The first cycle Coulombic efficiency is 93.8%, and the reversible specific capacity at 5C is 140 mAh g – 1 . Fig.12 The Ti obtained in Example 3 1.6 Nb 1.52 Cycling performance of O7 / Li half-cell at 5C rate. Active material loading is 5.05 mg cm – 2 Ti 1.6 Nb 1.52 The capacity retention rate of the O7 / Li half-cell after 500 cycles at 5C is 87.9% (refer to the second cycle).

[0082] Example 4: Preparation of high-titanium and low-niobium niobate by direct evaporation

[0083] 0.026 mol of titanyl sulfate and 0.0352 mol of ammonium niobium oxalate (hydrated) were dissolved in 300 mL of deionized water and stirred to form a uniform aqueous solution. 1.3 Nb 1.76 O7 precursor powder. Place the above solution in a beaker, heat it in a water bath at 80°C and stir continuously. After the water in the beaker is completely evaporated, Ti 1.3 Nb 1.76 O7 precursor powder. The obtained precursor powder is placed in a muffle furnace and sintered at 1100℃ for 2 hours to obtain Ti 1.3 Nb 1.76 O7 particles. Use a 300 mesh sieve for sieving. The subsequent half-cell preparation and testing methods are the same as in Example 1.

[0084] Fig.13 The Ti obtained in Example 4 1.3 Nb 1.76 X-ray diffraction (XRD) pattern of O7 particles shows that Ti prepared by direct evaporation 1.3 Nb 1.76The O7 particles are single-phase sheared ReO3 type crystal structures, and have the same crystal structural units as TiNb2O7 (3×3 octahedrons connected in order by common edges and common points).

[0085] Fig.14 The Ti obtained in Example 4 1.3 Nb 1.76 Scanning electron microscope (SEM) photo of O7 particles shows that Ti 1.3 Nb 1.76 The particle size of O7 particles is between 0.5–4 μm. Fig.15 The Ti obtained in Example 4 1.3 Nb 1.76 Charge and discharge curves of O7 / Li half-cell at different rates. The active material loading is 4.95 mg cm – 2 Ti 1.3 Nb 1.76 The reversible specific capacity of the O7 / Li half-cell at 0.1C is 279 mAh g – 1 The first cycle coulombic efficiency is 90.8%, and the reversible specific capacity at 5C is 138 mAh g – 1 . Fig.16 The Ti obtained in Example 4 1.3 Nb 1.76 Cycling performance of O7 / Li half-cell at 5C rate. The active material loading is 4.95 mg cm – 2 Ti 1.3 Nb 1.76 The capacity retention rate of the O7 / Li half-cell after 500 cycles at 5C is 86.3% (refer to the second cycle).

[0086] Example 5: Preparation of high-titanium and low-niobium niobate by coprecipitation

[0087] 0.024 mol titanium chloride and 0.0368 mol niobium oxalate (hydrated) were dissolved in 300 mL of deionized water and stirred to form a uniform aqueous solution. 1.2 Nb 1.84 The above solution was stirred at a constant speed and ammonia was added continuously until precipitation was completely generated. The obtained precipitate was washed 3 times with distilled water and ethanol and dried to obtain Ti 1.2 Nb 1.84 O7 precursor powder. The obtained precursor powder is placed in a muffle furnace and sintered at 1000℃ for 8 hours to obtain Ti 1.2 Nb 1.84O7 porous microspheres. Use a 300 mesh sieve for sieving. The subsequent half-cell preparation and testing methods are the same as in Example 1.

[0088] Fig.17 Ti obtained in Example 5 1.2 Nb 1.84 X-ray diffraction (XRD) diagram of O7 porous microspheres shows that Ti 1.2 Nb 1.84 The O7 porous microspheres are a single-phase shear ReO3 type crystal structure, and have the same crystal structural unit as TiNb2O7 (3×3 octahedrons connected in order with common edges and common points). Fig.18 Ti obtained in Example 5 1.2 Nb 1.84 Scanning electron microscope (SEM) image of O7 porous microspheres shows that Ti 1.2 Nb 1.84 The primary particle size of O7 porous microspheres is between 0.2–0.6 μm, and the secondary particle size is between 0.8–2.5 μm. Fig.19 Ti obtained in Example 5 1.2 Nb 1.84 Charge and discharge curves of O7 / Li half-cell at different rates. The active material loading is 5.03 mg cm – 2 Ti 1.2 Nb 1.84 The reversible specific capacity of the O7 / Li half-cell at 0.1C is 280 mAh g – 1 The first cycle Coulombic efficiency is 90.7%, and the reversible specific capacity at 5C is 131 mAh g – 1 . Fig. 20 Ti obtained in Example 5 1.2 Nb 1.84 Cycling performance of O7 / Li half-cell at 5C rate. The active material loading is 5.03 mg cm – 2 Ti 1.2 Nb 1.84 The capacity retention rate of the O7 / Li half-cell after 500 cycles at 5C is 85.5% (refer to the second cycle).

[0089] Comparative Example 1: Preparation of TiNb2O7 micron particles by conventional solid phase sintering method

[0090] 0.01 mol of titanium dioxide and 0.02 mol of niobium pentoxide (molar ratio of 1:2) were placed in a ball mill with a volume of 70 mL and ground in a high-energy ball mill (SPEX 8000M) for 1 hour. The ground mixture was sintered at 1200°C in a muffle furnace for 4 hours to obtain TiNb2O7 micron particles. A 300 mesh sieve was used for sieving. The subsequent half-cell preparation and testing methods were the same as in Example 1.

[0091] Fig.21 The XRD diagram of the TiNb2O7 micron particles obtained in Comparative Example 1 shows that the TiNb2O7 micron particles prepared by the traditional solid phase sintering method have a single-phase shear ReO3 type crystal structure (the crystal structure unit is 3×3 octahedrons connected in order with common edges and points). Fig. 22 This is a scanning electron microscope photograph of the TiNb2O7 micron particles obtained in Comparative Example 1. It can be seen that the particle size of the TiNb2O7 micron particles is between 1-5 μm. Fig.23 The charge and discharge curves of the TiNb2O7 / Li half-cell obtained in Comparative Example 1 at different rates. The active material loading is 4.92 mg cm – 2 The reversible specific capacity of the TiNb2O7 / Li half-cell at 0.1C is 268 mAh g – 1 The first cycle Coulombic efficiency is 96.1%, and the reversible specific capacity at 5C is 177 mAh g – 1 . Fig.24 The cycling performance diagram of the TiNb2O7 / Li half-cell obtained in Comparative Example 1 at a rate of 5C. The active material loading is 4.92 mg cm – 2 The capacity retention rate of the TiNb2O7 / Li half-cell after 500 cycles at 5C is only 33.6% (refer to the second cycle). Its poor cycling performance is mainly due to the excessive size of the TiNb2O7 micron particles. Comparative Example 2: Preparation of TiNb2O7 porous microspheres by spray drying

[0092] The spray drying process for preparing TiNb2O7 porous microspheres was the same as in Example 1, except that 0.02 mol titanyl sulfate and 0.04 mol niobium oxalate (hydrated) were used. The subsequent half-cell preparation and testing methods were the same as in Example 1.

[0093] Fig.25 The XRD pattern of the TiNb2O7 porous microspheres obtained in Comparative Example 2 shows that the TiNb2O7 porous microspheres prepared by spray drying are a single-phase shear ReO3 type crystal structure, but have the same 10 O 29The same crystal structure unit (3×4 octahedra connected in order with common edges and points). Fig.26 This is a scanning electron microscope photograph of the TiNb2O7 porous microspheres obtained in Comparative Example 2. It can be seen that the primary particle size of the TiNb2O7 porous microspheres is between 0.1-0.3 μm, and the secondary particle size is between 0.5-2 μm. Fig. 27 The charge and discharge curves of the TiNb2O7 / Li half-cell obtained in Comparative Example 2 at different rates. The active material loading is 4.71 mg cm – 2 The reversible specific capacity of the TiNb2O7 / Li half-cell at 0.1C is 265 mAh g – 1 , the first cycle Coulombic efficiency is 78.4%; there is almost no capacity at 5C, and the rate performance is very poor. The rate performance of the Ti1.5Nb1.6O7 porous microspheres in Example 1 is significantly better than that of the TiNb2O7 porous microspheres in Comparative Example 2, because Ti1.5Nb1.6O7 contains at least one of a large number of cation interstitials and oxygen ion vacancies, and these defects significantly improve the electrochemical kinetics.

[0094] Obviously, compared with the TiNb2O7 micron particles prepared by the traditional solid phase sintering method, the TiNb2O7 micron particles prepared by the liquid phase method based on the precursor solution are 1.5 Nb 1.6 The reversible specific capacity, first-cycle coulombic efficiency and rate performance of O7 material (representative material of niobate with more titanium and less niobium) are comparable, but the cycle performance is significantly improved and the niobium content is reduced by 17%. The above series of advantages of high safety performance, first-cycle coulombic efficiency, specific capacity, rate performance and cycle performance as well as low cost fully demonstrate that niobate with more titanium and less niobium is a promising negative electrode material for lithium-ion batteries.

[0095] The high-titanium and low-niobium niobates were prepared by a liquid phase method based on a precursor solution. Examples 6-24 are shown in Table 1.

[0096] Table 1

[0097]

[0098] Example 25: Carbon coating of high-titanium and low-niobium niobate

[0099] The Ti obtained in Example 1 1.5 Nb 1.6 TiO7 porous microspheres and lactose were mixed in deionized water at a mass ratio of 10:1. 1.5 Nb 1.6O7 porous microspheres, 0.04g lactose, 30mL deionized water. The above slurry was placed in a beaker, heated in a water bath at 80°C and stirred continuously. After the water in the beaker was completely evaporated, carbon-coated Ti 1.5 Nb 1.6 O7(C-Ti 1.5 Nb 1.6 The obtained precursor powder is placed in a tube furnace and heat treated at 800℃ for 2h in an Ar atmosphere to obtain C-Ti 1.5 Nb 1.6 O7 porous microspheres (carbon content 1.5 wt%) were sieved using a 300 mesh sieve.

[0100] The subsequent half-cell preparation and testing methods are the same as those in Example 1.

[0101] Fig.28 The C-Ti obtained in Example 25 1.5 Nb 1.6 Transmission electron microscope (TEM) image of O7 porous microspheres shows that C-Ti 1.5 Nb 1.6 The thickness of the carbon coating of O7 is about 3 nm. Fig.29 The C-Ti obtained in Example 25 1.5 Nb 1.6 Charge and discharge curves of O7 / Li half-cell at different rates. The active material loading is 4.98 mg cm – 2 C-Ti 1.5 Nb 1.6 The reversible specific capacity of the O7 / Li half-cell at 0.1C is 325 mAh g – 1 The first cycle Coulombic efficiency is 95.5%, and the reversible specific capacity at 5C is as high as 204 mAh g – 1 The rate performance is significantly better than that of C-Ti in Example 1. 1.5 Nb 1.6 O7 porous microspheres, because carbon coating improves Ti 1.5 Nb 1.6 The conductivity between O7 particles is greatly improved, thereby significantly improving the electrochemical kinetics. Fig.30 The C-Ti obtained in Example 25 1.5 Nb 1.6 Cycling performance of O7 / Li half-cell at 5C rate. The active material loading is 4.98 mg cm – 2 C-Ti 1.5 Nb 1.6The capacity retention rate of the O7 / Li half-cell after 500 cycles at 5C was 87.1% (refer to the second cycle).

[0102] Example 26: LiNi 0.5 Mn 1.5 O4 / Ti 1.5 Nb 1.6 O7 Full Battery

[0103] Using Ti of Example 1 1.5 Nb 1.6 O7 porous microspheres are used as negative electrode materials, commercial LiNi 0.5 Mn 1.5 O4 is the positive electrode material. 92wt% Ti 1.5 Nb 1.6 O7 porous microspheres, 4 wt% binder (polyvinylidene fluoride) and 4 wt% conductive carbon (acetylene black) were added to N-methylpyrrolidone and mixed to prepare a slurry. The slurry was coated on one side of a copper foil current collector and dried. The fully dried electrode was rolled to obtain an active material loading of 18–20 mg cm – 2 Ti 1.5 Nb 1.6 O7 negative electrode. LiNi 0.5 Mn 1.5 O4 cathode and Ti 1.5 Nb 1.6 The preparation method of the O7 negative electrode is the same, except that aluminum foil is used as the current collector. The ratio of the negative electrode capacity to the positive electrode capacity is 1.1:1. Then, a CR2032 full battery is assembled, in which the electrolyte is obtained by dissolving 1M lithium hexafluorophosphate in a mixed solvent of ethylene carbonate / diethylene carbonate / dimethyl carbonate (volume ratio is 1:1:1), and the separator is a Cegard 2400 polypropylene film. The electrochemical test temperature is about 25°C. For each cycle of electrochemical testing, the voltage window is 1.5–3.5V, the charge rate (charge current density) and the discharge rate (discharge current density) are equal, and 1C is set to 140mA g – 1 .

[0104] Fig.31 LiNi obtained in Example 26 0.5 Mn 1.5 O4 / Ti 1.5 Nb 1.6 The charge and discharge curves of the O7 full battery at different rates. The reversible specific capacity of the full battery at 0.5C is 137 mAh g – 1 , the reversible specific capacity at 7C is 75 mAh g – 1 . Fig.32 LiNi obtained in Example 26 0.5 Mn 1.5 O4 / Ti 1.5 Nb 1.6 The cycling performance of the O7 full battery at 7C rate. The capacity retention rate of the full battery at 7C was 86.4% after 4000 cycles (refer to the second cycle). It can be seen that lithium-ion batteries based on high-titanium and low-niobium niobate negative electrodes can have superior electrochemical performance.

[0105] It will be easily understood by those skilled in the art that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A single-phase niobate, characterized in that: Its general formula is Ti x Nb y O z ; Among them, 0.15≤x / z≤0.25 and 0.20≤y / z≤0.

28.

2. The single-phase niobate according to claim 1, characterized in that In the general formula, 0.171≤x / z≤0.215 and 0.228≤y / z≤0.

263.

3. The single-phase niobate according to claim 1 or 2, characterized in that: The single-phase niobate has a sheared ReO3 type crystal structure; Its crystal structure unit is a 3×3 octahedron connected in an orderly manner with common edges and points.

4. The single-phase niobate according to any one of claims 1 to 3, characterized in that Doping elements may be included.

5. A method for preparing a single-phase niobate according to any one of claims 1 to 4, characterized in that: The following steps are involved: (1) dissolving a titanium source and a niobium source in a solvent to obtain a mixed solution; (2) treating the mixed solution to obtain a precursor powder; (3) Sintering the precursor powder.

6. The preparation method according to claim 5, characterized in that: In step (1), the titanium source is a titanium compound soluble in water or alcohol; preferably, it is selected from titanyl sulfate, titanium chloride, tetraisopropyl titanate, and tetrabutyl titanate; the niobium source is a niobium compound soluble in water or alcohol; preferably, it is selected from niobium oxalate, ammonium niobium oxalate, niobium chloride, and niobium ethoxide; and the solvent is one or both of water and alcohol solvents.

7. The preparation method according to claim 5 or 6, characterized in that: In step (2), the mixed solution is treated by spray drying, solvent thermal method, sol-gel method, direct evaporation or co-precipitation method.

8. The preparation method according to any one of claims 5 to 7, characterized in that: The precursor powder is sintered in a gaseous atmosphere selected from one or more of air, O2, N2, Ar, He, CO2, CO and H2; the sintering temperature is 700-1200°C and the sintering time is 0.5-24 hours.

9. A single-phase niobate active electrode material, characterized in that: The active electrode material comprises primary particles and / or secondary particles of the single-phase niobate according to any one of claims 1 to 4.

10. The single-phase niobate active electrode material according to claim 9, characterized in that: The average size of the primary particles is 10 nm to 10 μm; the average size of the secondary particles is 0.5 μm to 30 μm.

11. The single-phase niobate active electrode material according to claim 9 or 10, characterized in that: The active electrode material comprises a carbon layer formed on the surface of primary particles and / or secondary particles.

12. The single-phase niobate active electrode material according to claim 11, characterized in that: The mass of the carbon layer is less than 5wt% of the total mass of the active electrode material; preferably, less than 2wt%; most preferably, less than 1wt%.

13. The single-phase niobate active electrode material according to any one of claims 9 to 12, characterized in that: Also contains Li.

14. A single-phase niobate active electrode material according to any one of claims 9 to 13, characterized in that: The preparation method includes one or more of the following post-processing steps: (1) heat treating the single-phase niobate; (2) Carbon coating of single-phase niobate; (3) mixing single-phase niobate with a conductive material; (4) Grinding single-phase niobate to change the particle size of the active electrode material.

15. Use of the single-phase niobate according to any one of claims 1 to 4 or the single-phase niobate active electrode material according to any one of claims 9 to 14 as a negative electrode material or as a component of a negative electrode material in a lithium ion battery.

16. An electrochemical device comprising a negative electrode, a positive electrode, and an electrolyte and a separator arranged between the negative electrode and the positive electrode, characterized in that: The negative electrode comprises the single-phase niobate according to any one of claims 1 to 4 or the single-phase niobate active electrode material according to any one of claims 9 to 14.

Citation Information

Patent Citations

  • Electrode material of secondary lithium ion battery, and its preparation method

    CN102983316A

  • Active material, nonaqueous electrolyte battery and battery pack

    CN105428635A

  • Electrode, nonaqueous electrolyte battery, and battery pack

    CN105990576A

  • In-situ carbon-coated titanium niobate composite material, and preparation method and application thereof

    CN112701260A

  • Carbon-coated niobium-doped modified titanium niobate material and preparation method thereof

    CN112736250A

Cited By

  • Single-phase niobate and active electrode material, and preparation methods therefor and use thereof

    WO2026114304A1